Synovial immunopathology in haemochromatosis arthropathy. Issue 6 (23rd November 2009) - Heiland, Gisela Ruiz; Aigner, Elmar; Dallos, Tomáš; Sahinbegovic, Enijad; Krenn, Veit; Thaler, Christoph; Weiss, Günter; Distler, Jörg H; Datz, Christian; Schett, Georg; Zwerina, Jochen
Abstract : Background: Hereditary haemochromatosis (HH) is a common autosomal recessive inherited disorder that frequently causes arthritis. The pathophysiology of musculoskeletal involvement is, however, unclear. Objective: To analyse synovial tissue obtained at surgery from patients with HH arthropathy and compare it qualitatively and quantitatively with specimens from patients with rheumatoid arthritis (RA) and osteoarthritis (OA). Methods: Synovial tissue from 15 patients with HH, 20 with RA and 39 with OA was obtained during surgery. A synovitis grading system was used to determine the severity of synovial inflammation. Using immunohistochemistry, synovial neovascularisation and infiltration of macrophages, neutrophils and lymphocytes were quantitatively assessed. Results: Synovitis in HH arthropathy largely resembles OA with mild infiltration of mononuclear cells and lymphocytes, formation of synovial microvessels and a low degree of synovial hyperplasia. While many features of HH arthropathy are reminiscent of OA, macrophage and especially neutrophil invasion is clearly more prominent in HH arthropathy than in primary OA and mimics features of RA. This finding was observed particularly in synovial tissue of HH samples with marked haemosiderin deposition. Discussion: The histological picture of the synovium in HH arthropathy largely resembles a process reminiscent of OA. Neutrophil invasion is, however, markedly increased in HH arthropathy, especially in joints with iron deposition. Accumulation of neutrophils may be crucial for the production of matrix enzymes, which enables cartilage degradation and more rapidly progressive articular damage.